Efeito da abreviação do jejum pré-operatório com carboidratos e proteínas hidrolisadas na resposta orgânica de pacientes submetidos à operações de grande porte : estudo randomizado e controlado - Machado, Paula Pexe Alves (2012)
The abbreviation of preoperative fasting time with carbohydrate-rich and protein beverage promotes important benefits for surgical patients, with consequent improvement in postoperative recovery. OBJECTIVE: To investigate whether shortening preoperative fasting with carbohydrate solution containing hydrolyzed protein changes: the organic response to trauma, with emphasis on the acute phase inflammatory response; and clinical outcomes in patients undergoing major digestive tract operations. METHODS: A randomized clinical study was carried out, evaluating 22 adult patients of both sexes, undergoing several major surgeries in the digestive tract. Randomization of patients was performed with the assistance of a computer program, following the precepts of the CONSORT group. Patients were classified into two groups: Control Group and Study Group. Those who belonged to the Study Group received 400 ml of a beverage containing 11% protein (pea protein hydrolysate), 89% carbohydrates (maltodextrin 79% and 21% sucrose) and 0% fat (Providextra, Fresenius Kabi, Sao Paulo, Brazil) the night before and 200 ml over three hours preceding the operation, while the patients in Control Group fasted during the conventional 6-8 hours until the procedure. All patients followed the routine minimum fasting period of 6 hours for solid foods. Both groups had blood samples collected in the morning before the operation and the second day after surgery. After randomization patients who did not drink the solution in their group, or with important intraoperative intercurrence as severe hypotension, cardiorespiratory arrest, as well as those who had prolonged surgeries lasting over six hours were excluded . RESULTS: Overall mortality of the study was 4.5% (1 case) and this only in the Control Group. The duration of postoperative hospital stay was twice as long in the Control Group (14 [4-34] days versus 7 [4-17] dias; p = 0.04). In the comparison between groups a significant increase of the ratio PCR / albumin on day 2 postoperatively was observed in the Control Group compared to the Study Group (p = 0.000). Likewise, there was a significant drop in serum albumin in the Control Group compared to the Study Group (p = 0.000). CONCLUSION: The abbreviation of preoperative fasting tome to three hours using a solution containing carbohydrates and hydrolyzed proteins in patients undergoing major operations reduces the inflammatory response of acute phase on postoperative day 2 and decreases the length of postoperative hospital time.